Risk of second primary cancers in women diagnosed with endometrial cancer in German and Swedish cancer registries - Chen, Tianhui; Brenner, Hermann; Fallah, Mahdi (International journal of cancer, 2017)
Along with the increasing incidence and favorable prognosis, more women diagnosed with endometrial cancer may develop second primary cancers (SPCs). We aimed at investigating risk of SPCs after endometrial cancer in Germany and Sweden to provide insight into prevention strategies for SPCs. Endometrial cancer patients diagnosed at age ≥15 years in Germany during 1997-2011 and in Sweden nationwide during 1997-2012 were selected. Standardized incidence ratios (SIRs), calculated as the ratio of observed to expected numbers of cases, were used to assess the risk of a specific second cancer after endometrial cancer for both German and Swedish datasets. Among 46,929 endometrial cancer survivors in Germany and 18,646 in Sweden, overall 2,897 and 1,706 SPCs were recorded, respectively. Significantly elevated SIRs were observed in Germany for ovarian (SIR = 1.3; 95%CI:1.1-1.5) and kidney cancers [1.6 (1.3-1.8)], while in Sweden the SIRs were 5.4 (4.6-6.3) and1.4 (1.0-1.9), respectively. Elevated risk for second ovarian endometrioid carcinoma was pronounced after early (<55 years) onset endometrial cancer in Germany [9.0 (4.8-15)] and Sweden [7.7 (5.1-11)]. In Germany elevated risks were found for second ovarian endometrioid carcinoma after endometrioid histology of first endometrial cancer [6.3 (4.0-9.4)] and for second kidney cancer after clear cell histology of endometrial cancer [4.9 (1.6-11)]. We found exceptionally elevated risk of second ovarian endometrioid carcinoma after endometrial cancer of the same histology or of early onset. Risk for second kidney cancer was also increased, particularly after endometrial cancer of clear cell histology. Cancer prevention strategies should focus on these cancers after endometrial cancer diagnosis.
Gesehen am 18.10.2017